Pricing rice quality attributes and returns to quality upgrading in sub-Saharan Africa - Twine, Edgar E.; Ndindeng, S.A.; Mujawamariya, Gaudiose; Futakuchi, K. (Cambridge University Press, 2022)
The study applies parametric and nonparametric estimation methods to determine hedonic prices of rice quality attributes, and a partial equilibrium model to determine the payoff to investing in quality improvement in five countries in Sub-Saharan Africa. Results indicate that consumers are willing to pay price premiums for head rice, slender grains, peak viscosity, parboiled rice, and rice sold in urban markets. However, they strongly discount amylose content, rice with impurities and imported rice. Investing in quality improvement through amylose content reduction leads to net welfare gains with a benefit-cost ratio of 47.86 and internal rate of return of 90%.